(untitled) (Revista de Biología Marina y Oceanografía, 2018)
Mustelus lunulatus is the most important shark demersal species in the landings of the Ecuadorian artisanal fishery, this study was carried out to expand the knowledge about size, sex, type of growth (isometric or allometric) and reproductive aspects in males of the species. Biological traits of the sicklefin smooth-hound shark, M. lunulatus, caught in the Pacific coast of Ecuador were assessed by examining 199 individuals ranging from 41.2 to 135.0 cm in total length (TL). The means TL did not show significant differences between sexes. The sex ratio was not different from 1:1 and the weightlength relationship did not showed significant differences between males and females. Both sexes have a growth of isometric type (b males= 3.05 and b females= 3.15). Total length at sexual maturity (TL50) of male M. lunulatus, calculated from the clasper condition, was estimated to be 97.2 cm. The present study provides new information regarding the biology of M. lunulatus in Ecuadorian waters.